Effect of microplastic particle size to the nutrients removal in activated sludge system. (February 2021) - He, Yanjiao; Li, Lu; Song, Kang; Liu, Qun; Li, Zhouyang; Xie, Fazhi; Zhao, Xiaoli
Abstract: Microplastics as emerging environmental pollutants, its effect to the bioprocess of water and wastewater treatment has aroused concern. This study investigated the effects of microplastic polystyrene (PS) particle size to the activated sludge nutrient removal process. The ammonia, nitrite, nitrate and phosphorus removal under various PS particle size during nitrification and denitrification process was tested. The results indicated that with PS particle size 150–300 μm, the ammonia oxidation during nitrification process was inhibited to 71%, 92%, and 80% as compared with the blank reactor, for PS concentration at 0.01 g/L, 0.05 g/L and 0.10 g/L, respectively. The nitrite accumulation during nitrification process was also high at PS particle size 150–300 μm and concentration no less than 0.05 g/L. The nitrate reduction during the denitrification process was all inhibited to 69%–94% as compared with the blank, except for reactor No.4. The phosphate removal during nitrification process was not affected by the existence of microplastics PS, the average removal rate was over 80% after 2 h and over 95% after 3 h, respectively. The microplastics particle size plays important role in affecting the activated sludge nutrient removal process. Highlights: Microplastics particle size plays important role to activated sludge nutrients removal. In particle size 150–300 μm, activated sludge nitrification process was inhibited. Phosphate removal during denitrification process was not affected by microplastic.